The phase diagram of K0.5Na0.5NbO3–Bi1/2Na1/2TiO3. Issue 2 (24th March 2016) - Liu, Laijun; Knapp, Michael; Ehrenberg, Helmut; Fang, Liang; Schmitt, Ljubomira Ana; Fuess, Hartmut; Hoelzel, Markus; Hinterstein, Manuel
Abstract : The phase diagram of K0.5 Na0.5 NbO3 –Bi1/2 Na1/2 TiO3 is reported. Abstract : The phase diagram of the lead‐free piezoelectric (1 −  x )K0.5 Na0.5 NbO3 – x Bi1/2 Na1/2 TiO3 system has been studied by high‐resolution synchrotron powder diffraction, neutron powder diffraction and selected area electron diffraction. The two lead‐free piezoelectric materials K0.5 Na0.5 NbO3 and Bi1/2 Na1/2 TiO3 form an infinite substitution solid solution. The orthorhombic ( O ), monoclinic ( M ), tetragonal ( T ) and rhombohedral ( R ) phases and the phase coexistence of M ( Pm ) + T ( P 4 mm ) for 0.02 < x ≤ 0.14, T ( P 4 bm ) + pseudocubic ( ) for 0.14 < x ≤ 0.87 and T ( P 4 bm ) + R ( R 3 c ) for 0.87 < x ≤ 0.96 have been investigated at room temperature, with a subtle change in the structure observed. The oxygen octahedral tilt system has been mapped as a function of composition and temperature. The results indicate that K0.5 Na0.5 NbO3 –Bi1/2 Na1/2 TiO3 does not display a morphotropic phase boundary like lead zirconate titanate, and that the most significant structural changes as a function of composition occur near x = 0.14 and x = 0.87 as a result of ionic disorder at the A and B sites in the perovskite AB O3 structure at room temperature.